2013 IEEE MTT-S International Microwave Symposium Digest (MTT) 2013
DOI: 10.1109/mwsym.2013.6697367
|View full text |Cite
|
Sign up to set email alerts
|

Quantization noise cancelation scheme for digital quadrature RF pulse encoding

Abstract: Quadrature type pulsed radio frequency (RF) signal encoding combined with class-S switched-mode power amplification (SMPA) constitute a potential solution for high efficiency RF transmitters. However, the digital center frequency adjustment for such encoding methods is limited by quantization noise folding. In this paper, a novel quantization noise cancelation scheme is proposed that in an ideal case suppresses the folding distortion components completely. In addition, a low complexity practical solution easil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…For a single carrier environment, an increase in offset frequency also increases the unwanted spectral components. More other literatures, Routsalainen et al in [7,8] showed that larger frequency offsets caused image noise to fold in-band. They investigated a solution using complex noise shaping filters to move the main noise null and suppressing the image noise [7] and then another solution by using a fractional delay in the feedback path [8].…”
Section: Introductionmentioning
confidence: 87%
“…For a single carrier environment, an increase in offset frequency also increases the unwanted spectral components. More other literatures, Routsalainen et al in [7,8] showed that larger frequency offsets caused image noise to fold in-band. They investigated a solution using complex noise shaping filters to move the main noise null and suppressing the image noise [7] and then another solution by using a fractional delay in the feedback path [8].…”
Section: Introductionmentioning
confidence: 87%